Organizational Culture in Philosophical Review: Ontology, Epistemology, and Axiology - Sudrajat, Jajat; Siow, Hong Loke; Permana, Ibar Adi (Perkumpulan Psikologi Transformasi Indonesia (P2TI), 2024)
The cultural dimension of organizational culture is the centre of all aspects of an organization's life. This research aims to describe organizational culture in philosophical terms. This research uses a qualitative method with a literature study approach. Literature documents come from various books, journals and scientific works on organizational culture. This research shows that ontologically describing organizational culture is indeed proven to exist. In the epistemological aspect, it is related to knowledge, sources, characteristics, truth, and ways to show the existence of organizational culture in an organization. In the etymology aspect, organizational culture focuses on the sources scientists use in developing organizational culture and their methods. Ultimately, the axiology aspect discusses the relationship between organizational culture and values. Because it is related to values, axiology is related to whether or not organizational culture can be developed. Educational entities must pay attention to organizational culture to ensure the continued existence and success.